(untitled) (Journal of Applied Juvenile Justice Services, 2021)
Yoga has been making its way into juvenile detention centers, but little research has looked at the possible effects of yoga on this special population of individuals. The purpose of this paper is to review the relevant literature available on the effects of yoga on youth involved with the justice system and its po-tential for rehabilitation. Notably, the objective here is to highlight the need for gender-specific program-ming, specifically those designed with women and girls in mind. This paper takes a gender-responsive and trauma-informed approach when discussing literature on alternative rehabilitation and, importantly, identifies the gaps in previous research while offering ways of improvement. The findings in this review highlight the need for trauma-informed care and gender-specific programming. Importantly, this review identifies the need for race-sensitive programming while addressing cultural, historical, and gender-based issues within the field of criminology and criminal justice. Overall, we find that gender-specific programs are useful but lack in implementation and program evaluation. With that said, more research is needed in this area of study.